PATHOGENETIC APPROACH IN TREATMENT BRONCHIAL ASTHMA IN CHILDREN - Barno T. Khalmatova,; Gulnoza A. Tashmatova, (Central Asian Journal of Medicine, 2023)
The article presents data on the clinical trials of local production of Montelukast (Republic of Uzbekistan). The purpose of the study is to assess the clinical efficacy and tolerability of montelukast preparations produced in Uzbekistan, in comparison with the drug Singlon, produced by Gedeon Richter JSC (Hungary). Methods. The clinical study was limited, comparative, open, controlled, randomized with four parallel groups. Studies were conducted in patients who are hospitalized in the pulmonology and allergology departments of the clinic of the Tashkent Medical Academy. The study involved 150 children aged 2 to 14 years with a diagnosis of intermittent, mild and moderate persistent bronchial asthma. Results: The clinical efficacy of the drugs was assessed in points for the improvement of clinical and laboratory data. The study showed a positive dynamics of clinical and laboratory parameters in all children who received Montelukast drugs. Conclusion. Studies have shown that local production montelukast is not inferior in its properties to foreign analogues and leads to a decrease in the level of cys-LT, IgE in children with asthma.